2017
DOI: 10.2196/jmir.6712
|View full text |Cite
|
Sign up to set email alerts
|

Therapist-Supported Internet-Based Cognitive Behavior Therapy for Stress, Anxiety, and Depressive Symptoms Among Postpartum Women: A Systematic Review and Meta-Analysis

Abstract: BackgroundA growing number of meta-analyses have supported the application of therapist-supported Internet-based cognitive behavior therapy (iCBT) for psychological disorders across different populations, but relatively few meta-analyses have concentrated on postpartum women.ObjectiveThis meta-analysis evaluated the efficacy of therapist-supported iCBT in improving stress, anxiety, and depressive symptoms among postpartum women.MethodsA total of 10 electronic databases were used to search for published and unp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 55 publications
(211 reference statements)
7
98
0
2
Order By: Relevance
“…For example, Matvienko-Sikar and Dockrey (2017) piloted a gratitude and mindfulness intervention with significant effects on stress, but not on life satisfaction. Internet interventions that target SWB during pregnancy are less common, but studies do suggest the merits of preventive interventions for decreasing depressive symptoms, stress, and anxiety in postpartum women (Lau et al, 2017). The changes in negative affect in this study may reflect the unique ability of the 'Mamma Mia' intervention to foster self-regulation of negative feelings rather than construct new positivity (Aspinwall & Tedeschi, 2010).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…For example, Matvienko-Sikar and Dockrey (2017) piloted a gratitude and mindfulness intervention with significant effects on stress, but not on life satisfaction. Internet interventions that target SWB during pregnancy are less common, but studies do suggest the merits of preventive interventions for decreasing depressive symptoms, stress, and anxiety in postpartum women (Lau et al, 2017). The changes in negative affect in this study may reflect the unique ability of the 'Mamma Mia' intervention to foster self-regulation of negative feelings rather than construct new positivity (Aspinwall & Tedeschi, 2010).…”
Section: Discussionmentioning
confidence: 78%
“…Perinatal women use the internet frequently to search for information pertaining to pregnancy and postnatal topics and a recent systematic review suggests that the use of eHealth technology has the potential to transform the perinatal healthcare system (Van den Heuvel et al, 2018). In terms of perinatal mental health, there are recent studies on internet interventions that demonstrate their usability (Danaher et al, 2012;Haga et al, 2013;Salonen et al, 2014) and effectiveness in reducing perinatal depressive symptoms (Ashford et al, 2016;Haga et al, 2018;Lau et al, 2017;Lee et al, 2016). At present, however, no systematic effort aimed at enhancing SWB among perinatal women exists.…”
Section: Introductionmentioning
confidence: 99%
“…RCTs of interventions using new mo‐dalities for delivery, namely online CBT or behavioural activation, for perinatal depression have also demonstrated robust effects in several countries 83‐85 .…”
Section: Interventionsmentioning
confidence: 99%
“…The study found that therapist-supported internet based CBT significantly improved stress, anxiety, and depressive symptoms among postpartum women (Lau et al 2017).…”
Section: Estrogens:-mentioning
confidence: 88%